2018
DOI: 10.18267/j.pep.664
|View full text |Cite
|
Sign up to set email alerts
|

What Do Post-Communist Countries Have in Common When Predicting Financial Distress?

Abstract: Business failure prediction is an important issue in corporate finance. Different prediction models are proposed by financial theory and are often used in practice. Their application is effortless, selecting only few key inputs with the greatest informative power from the large list of possible indicators. Our paper identifies the financial distress predictors for 5 post-communist countries (Bulgaria, Croatia, the Czech Republic, Hungary and Romania) based on information collected from the Amadeus database for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Many authors give business failure a legal definition of bankruptcy [48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Others, instead, define business failure as financial difficulties in meeting a company's obligations [62][63][64][65][66][67]. Altman [48] initially considered as examples of business failure those firms that were legally in bankruptcy; in contrast, in a later study conducted in 1988, he indicated as business failure cases those companies that were in a situation of insolvency or inability to meet their obligations.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors give business failure a legal definition of bankruptcy [48][49][50][51][52][53][54][55][56][57][58][59][60][61]. Others, instead, define business failure as financial difficulties in meeting a company's obligations [62][63][64][65][66][67]. Altman [48] initially considered as examples of business failure those firms that were legally in bankruptcy; in contrast, in a later study conducted in 1988, he indicated as business failure cases those companies that were in a situation of insolvency or inability to meet their obligations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is important to point out that none of these issues was found in the first subperiod, so it can be stated that they cannot be considered decadent. The appearance of financial distress is due to research [6,62,64,[153][154][155] examining the strategies that companies choose when faced with financial difficulties before reaching the stage of financial insolvency or business failure and how such difficulties affect the probability of recovery.…”
Section: Content Analysis 421 Research Trendsmentioning
confidence: 99%
“…To prediction, they used 10 different approaches including decision trees C5.0, CART, QUEST and CHAID. In their paper, Popescu and Dragotă (2018) identify the business failure predictors for 5 post-communist countries (Bulgaria, Croatia, the Czech Republic, Hungary and Romania) using CHAID decision tree and neural networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Among machine learning methods based on artificial intelligence, artificial neural networks and decision trees are the most commonly used techniques [5]. In 2018, Popescu and Dragotă [6] identified the financial distress predictors for five post-communist countries (Bulgaria, Croatia, the Czech Republic, Hungary and Romania) using CHAID decision tree and neural networks. In Slovakia, Gavurova [7] and Karas and Reznakova [8] developed prediction models using decision trees.…”
Section: Literature Reviewmentioning
confidence: 99%